Lethal Clostridium difficile Colitis Associated with Paclitaxel and Carboplatin Chemotherapy in Ovarian Carcinoma: Case Report and Review of the Literature. (5th July 2010) - Masciullo, V.; Mainenti, S.; Lorusso, D.; Margariti, P. A.; Scambia, G.
Abstract : Clostridium difficile colitis, although rare, could represent a serious complication following chemotherapy. Prior antibiotic use has been considered the single most important risk factor in the development of C. difficile infection. Recently, the association between antineoplastic therapy and C. difficile -associated diarrhea in the absence of a prior antibiotic therapy has become more apparent. A 75-year-old woman with serous adenocarcinoma of the ovary developed lethal pancolitis caused by C. difficile after five cycles of paclitaxel- and carboplatin-based chemotherapy. She presented with diarrhea, coffee-ground emesis, and oliguria and was hospitalized immediately for aggressive treatment. Despite all the medical efforts, her condition worsened and she died after twenty days. We describe the second case reported of a patient developing a severe C. difficile colitis following chemotherapy without any recent antibiotic use and review the data of the literature, emphasizing the need to a prompt diagnosis and management that can significantly decrease the morbidity and life-threatening complications associated with this infection.